POTENSI POHON KENARI (Canarium indicum) PADA DESA EMA KECAMATAN LEITIMUR SELATAN KOTA AMBON - Doortjie J. Ubro; Ludia Siahaya; Hendrik S. E. S. Aponno (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aims to examine the ecological and economic potential of Walnuts trees (Canarium indicum) in Ema Village, South Leitimur District, Ambon City. Data collection was conducted on 17 plots covering an area of ​​0.68 Ha using a census method for all Walnuts individuals, as well as measurements of environmental factors including light intensity, air temperature, soil pH, soil fertility, and soil moisture. Socio-economic data were collected through interviews with Walnuts farmers. The results of the study indicate that the ecological conditions of Ema Village are at an altitude of 201 meters above sea level, undulating topography, and soil with good drainage, temperature, humidity, and soil pH that support so that Walnuts plants can grow well with the largest number of individuals at the tree, pole, and sapling growth levels. The total stand volume reached 41.39 m³ (Rp. 41,390,000). The average production reached 50 kg of fresh fruit per tree per year from 66 productive trees with a total of 3300 kg of fresh fruit/year, producing 1320 kg of kernels after peeling. The potential economic value reaches Rp 64,350,000 in net income per year. Overall, canaries have significant potential to be developed as a leading commodity that supports increased community income and environmental conservation in Ema Village.